Achieving High‐Performance Oxygen Reduction Catalyst and Zn–Air Battery through a Synergistic Nitrogen Doping Strategy. Issue 11 (2nd November 2022) - Zhu, Xiaoran; Zhang, Jianze; Wang, Yan; Yang, Mingsheng; Yu, Haiping; Li, Tengfei; Hu, Mingjun; Yang, Jun
Abstract : The catalyst obtained through the synergistic nitrogen doping of Fe‐tpphz and g‐C3 N4 greatly enhances the oxygen reduction reaction dynamics, enabling excellent performance of a Zinc‐air battery. With the "irrigation" of the catalyst, "fruitful" products on the tree rooted from the Zinc‐air battery can be reaped, to achieve a greener and healthier life. More details can be found in article number 2200602, Mingjun Hu, Jun Yang, and co‐workers.